Hybrid technique for laparoscopic incisional ventral hernia repair combining laparoscopic primary closure and mesh repair. Issue 3 (August 2014) - Yoshikawa, Kozo; Shimada, Mitsuo; Kurita, Nobuhiro; Sato, Hirohiko; Iwata, Takashi; Higashijima, Jun; Chikakiyo, Motoya; Nishi, Masaaki; Kashihara, Hideya; Takasu, Chie; Matsumoto, Noriko; Eto, Syohei
Abstract Introduction Incisional ventral hernia is one of the most common surgical complications after laparotomy. Laparoscopic repair of incisional ventral hernia has been conducted recently, and the advantages of this procedure have been reported. However, in large orifice cases, the recurrence rate is increased. To improve recurrence rates in large cases, a hybrid method combining laparoscopic primary closure and mesh repair can be applied. Materials and Surgical Technique Monofilament thread was inserted into the abdominal cavity for hernia closure and pulled from the other side of the orifice. The same procedure was performed from the upper side to the lower side without closure, and all thread was placed in line. Both sides of the thread were then introduced to the midline of the incision through a subcutaneous route. This procedure was conducted with an introducer. All threads were tied, and then a mesh was placed. Discussion Hybrid techniques already combine mini‐laparotomy for hernia closure and subsequent laparoscopic intraoperative onlay mesh for reinforcement, but such techniques require laparotomy. In our technique, closure of the linea alba does not require laparotomy. All procedures were performed laparoscopically. This procedure is very easy and safe, and does not require the abdominal cavity to be opened. Thus, hybrid methods are effective for treating cases of incisional hernia involving a large orifice.